2004
DOI: 10.1007/s00403-003-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological features of peripilar signs associated with androgenetic alopecia

Abstract: PPS could be the clinical signs reflecting the presence of perifollicular infiltrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 17 publications
8
76
2
7
Order By: Relevance
“…This feature, called by some authors "hyperpigmentation" or "peripilar sign" is reflecting the presence of perifollicular lymphocytic infiltrates in early androgenic alopecia. 17 Our results confirm the presence of perifollicular discoloration also in healthy persons.…”
Section: Discussionsupporting
confidence: 84%
“…This feature, called by some authors "hyperpigmentation" or "peripilar sign" is reflecting the presence of perifollicular lymphocytic infiltrates in early androgenic alopecia. 17 Our results confirm the presence of perifollicular discoloration also in healthy persons.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, female hair follicle appeared more active in prostaglandin synthesis than male one as shown by a significant difference (P < 0.01) with respect to mPGES-2 and AKR1C3 ⁄ PGFS gene expression. Considering the potential role of prostaglandins in hair growth and hair cycle control, one thus could speculate that such sexual difference might somehow be linked to the difference observed between males and females with regards to alopecia prevalence (23). Although the origin of these hair follicle sex-related differences remained unknown, it has however been reported that steroids could have, in some tissues, specific influence on prostaglandin level.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca TE'de de gözlenebilir (6,7,11). Erken dönem AGA'da perifoliküler lenfositik infiltrat varlığıyla ilişkili olduğu gösterilmiştir (24). Ancak sağlıklı kişilerde de bu bulgu frontal bölgede %25 oranına varacak şekilde saptanabilir (8).…”
Section: Perifoliküler Epidermisunclassified